2022
DOI: 10.3389/fimmu.2022.897971
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent Lupus Blautia (Ruminococcus) gnavus strain induction of zonulin-mediated intestinal permeability and autoimmunity

Abstract: Imbalances in the gut microbiome are suspected contributors to the pathogenesis of Systemic Lupus Erythematosus, and our studies and others have documented that patients with active Lupus nephritis have expansions of the obligate anaerobe, Blautia (Ruminococcus) gnavus (RG). To investigate whether the RG strains in Lupus patients have in vivo pathogenic properties in a gnotobiotic system, we colonized C57BL/6 mice with individual RG strains from healthy adults or those from Lupus patients. These strains were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Relevant, faecal transplants from mice with lupus-like glomerulonephritis into germ-free mice are reported to induce an inflammatory autoimmune condition,36 reiterating earlier findings reported for a murine gut pathobiont isolate 37. Notably, in vivo murine colonisation with the LG-expressing RG strains, S107-48 and S47-18, from LN patients, which express the LG previously shown to include potent TLR2 stimulatory activity,7 was also shown to induce severe impairment of the intestinal barrier 33. Neonatal colonisation with the S107-48 strain led to RG translocation into draining mesenteric lymph nodes, and induction of serum IgG anti-DNA antibodies at levels proportional to the induced functional impairment of the gut barrier 33.…”
Section: Discussionsupporting
confidence: 71%
“…Relevant, faecal transplants from mice with lupus-like glomerulonephritis into germ-free mice are reported to induce an inflammatory autoimmune condition,36 reiterating earlier findings reported for a murine gut pathobiont isolate 37. Notably, in vivo murine colonisation with the LG-expressing RG strains, S107-48 and S47-18, from LN patients, which express the LG previously shown to include potent TLR2 stimulatory activity,7 was also shown to induce severe impairment of the intestinal barrier 33. Neonatal colonisation with the S107-48 strain led to RG translocation into draining mesenteric lymph nodes, and induction of serum IgG anti-DNA antibodies at levels proportional to the induced functional impairment of the gut barrier 33.…”
Section: Discussionsupporting
confidence: 71%
“…The qPCR analysis also showed the dual effect of the microbiota origin and dietary tryptophan, with Rg abundance being higher in TCmbTrp lo than in B6mbTrp hi mice, and a similar trend between B6mbTrp hi and B6mbTrp lo mice. 16S rDNA sequence analysis cannot distinguish the LP-producing Rg pathobiont strain, Rg 2, from non-LP producing strain Rg1 47 . However, the growth of Rg2, but not Rg1, was enhanced by supplemental tryptophan in vitro ( Figure 4G-H ), suggesting that dietary tryptophan expand the Rg2 population present in the TC microbiota.…”
Section: Resultsmentioning
confidence: 96%
“…Recent reports, including ours, have shown that higher gut inflammation and permeability markers, calprotectin and zonulin (pre‐Hp2), are produced by SLE patients compared to healthy controls [51–53]. However, it is not known if these features are a consequence of the disease activities or occur prior to clinical stage disease.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, our observation that pre-Hp RNA levels and Hp protein levels can be detected in mice with higher gut permeability was intriguing. Of note, many reports have shown that a pre-HP2 inhibitory octapeptide (GGVLVQPG) called AT1001 could suppress gut permeability and suppress multiple clinical conditions in rodent models [52,[63][64][65][66]. However, it has been reported that neither human HP2 or mouse Hp harbours AT1001 sequence and it is an immunoglobulin sequence [67].…”
Section: Discussionmentioning
confidence: 99%